A High-Quality, Chromosome-Level Genome Provides Insights Into Determinate Flowering Time and Color of Cotton Rose (Hibiscus mutabilis) - Yang, Yuanzhao; Liu, Xiaodan; Shi, Xiaoqing; Ma, Jiao; Zeng, Xinmei; Zhu, Zhangshun; Li, Fangwen; Zhou, Mengyan; Guo, Xiaodan; Liu, Xiaoli (Frontiers in Plant Science, 2022)
Hibiscus mutabilis (cotton rose) is a deciduous shrub or small tree of the Malvaceae family. Here, we report a chromosome-scale assembly of the H. mutabilis genome based on a combination of single-molecule sequencing and Hi-C technology. We obtained an optimized assembly of 2.68 Gb with a scaffold N50 length of 54.7 Mb. An integrated strategy of homology-based, de novo, and transcriptome-based gene predictions identified 118,222 protein-coding genes. Repetitive DNA sequences made up 58.55% of the genome, and LTR retrotransposons were the most common repetitive sequence type, accounting for 53.15% of the genome. Through the use of Hi-C data, we constructed a chromosome-scale assembly in which Nanopore scaffolds were assembled into 46 pseudomolecule sequences. We identified important genes involved in anthocyanin biosynthesis and documented copy number variation in floral regulators. Phylogenetic analysis indicated that H. mutabilis was closely related to H. syriacus, from which it diverged approximately 15.3 million years ago. The availability of cotton rose genome data increases our understanding of the species’ genetic evolution and will support further biological research and breeding in cotton rose, as well as other Malvaceae species.